Critical Review of the Scientific Evidence and Recommendations in COVID-19 Management Guidelines. (14th July 2021) - Xie, Jiaxing; Wang, Zhufeng; Liang, Jingyi; Lin, Huimin; Yang, Zhaowei; Wang, Yingzhi; Liang, Hanwen; Wu, Hongkai; Chen, Ruchong; Ou, Younger; Wang, Fengyan; Wang, Yuan; et al.
Abstract: Background: Little is known about the quality and potential impacts of the guidelines for coronavirus disease 2019 (COVID-19) management. Methods: We systematically searched PubMed, Web of Science, Cochrane Library, guideline databases, and specialty society websites to evaluate the quality of the retrieved guidelines using the Appraisal of Guidelines for Research and Evaluation II. Results: A total of 66 guidelines were identified. Only 24% were categorized as "recommended" for clinical practice. The 211 identified recommendations for COVID-19 management were classified into 4 topics: respiratory support (27), acute respiratory distress syndrome management (31), antiviral or immunomodulatory therapy (95), or other medicines (58). Only 63% and 56% of recommendations were supported by, respectively, assessment of the strength of the recommendations or level of evidence. There were notable discrepancies between the different guidelines regarding the recommendations on COVID-19 management. Conclusions: The quality of the guidelines for COVID-19 management is heterogeneous, and the recommendations are rarely supported by evidence.